DNA grafting on silicon nanonets using an eco-friendly functionalization process based on epoxy silane. (2019) - Demes, Thomas; Morisot, Fanny; Legallais, Maxime; Calais, Adrien; Pernot, Etienne; Pignot-Paintrand, Isabelle; Ternon, Céline; Stambouli, Valérie
Abstract: A new glycidoxypropyltrimethoxysilane (GOPS) deposition process using chemical vapor phase at ambient pressure in anhydrous atmosphere has been successfully implemented on Si nanonets which are randomly oriented Si nanowire (NW) networks. As a result, a covalent grafting of DNA probes followed by DNA hybridization could be obtained. Compared to the usually used deposition of GOPS in liquid phase, this process is shorter in time, toxic solvent-free, with the same or better efficiency. Moreover, this simple, fast and eco-friendly functionalization process can advantageously replace the previously studied amino-propyltriethoxysilane (APTES) deposition process and is therefore well adapted for the fabrication of Si nanonet based DNA biosensors.